Peripheral odontogenic keratocyst: Clinicopathological and immunohistochemical characterization - Lafuente‐Ibáñez de Mendoza, Irene; Aguirre‐Urizar, José Manuel; Villatoro‐Ugalde, Verónica; Magaña‐Quiñones, José‐Julio; Lana‐Ojeda, Jessica; Mosqueda‐Taylor, Adalberto (Oral diseases, 2022)
Objective The aim of this study is to present and discuss the salient clinicopathological features, differential diagnosis and epithelial immunohistochemical profile of three additional cases of peripheral odontogenic keratocyst (POKC) and to present a review of the literature. POKC is a locally aggressive odontogenic lesion. The peripheral variant of the odontogenic keratocyst is rare and more frequently located in anterior gingiva. Material and Methods We present the clinicopathological features of 3 new cases of POKC (2 women and 1 man; age range: 14–74 years). Immunohistochemical study included CK7, CK14, CK19 and Ki‐67, and a systematic review of the literature was performed in PubMed, Scopus and Web of Science databases. Results All cases were located in the anterior gingiva (2 in maxilla and 1 mandible), and none corresponded to Gorlin–Goltz syndrome. High expression of CK14 was seen in all cases, with CK19 and CK7 been only focally positive. The expression of Ki‐67 was located in the basal and parabasal cells in all cases. Conclusions POKC is a rare gingival lesion that seems to originate from remnants of dental lamina or from the basal cells of the gingival epithelium and present a similar histopathology as compared to intraosseous OKC.